1984
DOI: 10.1128/mcb.4.12.2905
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of heavy-chain class switching and switch region deletion in an Abelson virus-transformed cell line.

Abstract: We demonstrated that a subclone of an Abelson murine leukemia virus-transformed B-lymphoid cell line switched from I. to '2b expression in vitro, by the classical recombination-deletion mechanism. In this line, the expressed VHDJH region and the Cy2b constant region gene were juxtaposed by a recombination event which linked the highly repetitive portions of the S,, and Sy2b regions and resulted in the loss of the C, gene from the intervening region. An additional recombination event in this subclone involved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…The ratio of productive and nonproductive transcripts was similar in all isotypes except ␣, indicating that in most of the CLL cells the two Ig H chain loci had switched to the same C H genes. This finding is in agreement with investigations in human and mouse B cell lines which have shown that the VDJ genes in both chromosomes frequently switch to genes that encode the same C H isotype (33,34).…”
Section: Discussionsupporting
confidence: 82%
“…The ratio of productive and nonproductive transcripts was similar in all isotypes except ␣, indicating that in most of the CLL cells the two Ig H chain loci had switched to the same C H genes. This finding is in agreement with investigations in human and mouse B cell lines which have shown that the VDJ genes in both chromosomes frequently switch to genes that encode the same C H isotype (33,34).…”
Section: Discussionsupporting
confidence: 82%
“…The location of the sites is taken from references 14-16, except for the Bcl I site, which was mapped in this study. The 5'-S.2b probe (5'S-Sy2b) is a 0.8-kb EcoRI-Bgl I fragment (17,18); the y2b cDNA probe is a Kpn I-BamHI fragment (19). normal switch variants with a y2b gene on the V2 allele.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of a large series of these isolates has shown that while all have begun or completed VHDJH joining 5' of Cp,u less than 5% have rearranged either K or A L-chain genes (3), reinforcing their relationship to normal pre-B lymphocytes. Several groups have described rare clones that undergo isotype switching accompanied by deletion, a phenomenon normally associated with more mature cells (10,14). Other rare clones (less than 5% of all isolates) express enhanced levels of ,.…”
Section: Discussionmentioning
confidence: 99%